I giovani e la comunicazione mediata dal computer: osservazioni linguistiche su nuove forme di alfabetizzazione - Gheno, Vera (Verbum – Analecta Neolatina, 2009)
This paper first presents some facts about the cultural background of young Italian people, showing subsequently a selection of the well-established characters of spoken and written juvenile Italian. Then it moves over to discuss the technological situation of Italy, also presenting a choice of widely recognized peculiarities of the language of Italian Computer-Mediated Communication (CMC) and showing that many of them are linked to a juvenile linguistic background. The paper then discusses the influence that computers and computermediated knowledge might have on the juvenile cultural world, presenting also some opinions about these two types of language (juvenile language and CMC), considered by some as marginal or even dangerous for the "integrity" of the Italian language. Regarding this issue, the author states - recalling a well-established scientific tradition - that the mostmature behavior would be to consider every variety of Italian - even the humblest - as equally relevant and linguistically interesting, although it is pivotal to use it in the right way and in the correct context.